Differentiation of Thermal Conditions in the Vertical Profile of Natural National Park of Carpathians - Mucha Bohdan; Kicińska Bożena; Wawer Jolanta (Miscellanea Geographica: Regional Studies on Development, 2008)
In the paper, the results of field studies using automatic meteorological stations are presented. The studies were conducted in July 2005 – July 2006 in the vertical profile of Natural National Park of Carpathians. The results show that the thermal conditions in the area under research is strongly differentiated. Particularly large differences have been observed between the lowerings of the terrain (where the range of annual air temperature changes reaches almost 70°C, exceptionally high and exceptionally low temperature occurs often, and thermal inversions are frequently encountered) and the summit region (where the range of annual air temperature changes barely exceeds 50°C and the mean changes of daily air temperature are consideraly smaller).